Russian historian A. L. Pogodin about Polish history and Polish question - Arzhakova, Larisa (Przegląd Wschodnioeuropejski, 2018)
The subjects of the study are works of A. L. Pogodin devoted to the history of Poland, reflected perception of the Polish question by the Russian society. Studying of his polonistic heritage allows us to speak with more confidence about the statement of the Russian historical polonistic in the first quarter of the 20th century, considering that, this problem remains until today debatable and demands amendments. Pogodin’s works have been analyzed from the point of view of both the essence and evolution of the Polish question, as well as those significant changes that occurred not only in the field of historical science, studying the history of Poland, but also the visions of the Russian society on Poland. This study gave the chance to come closer to understanding the Pogodin’s information code in his historical works, which allowing to shake basement of the Russian historical tradition concerning the Polish history of the 19th century.